EFEKTIVITAS PEMBERIAN MINUMAN ISOTONIK DAN AIR MINERAL DALAM MENDUKUNG PEMULIHAN KARDIOVASKULER, KAPASITAS AEROBIK MAHASISWA DI KABUPATEN BOJONEGORO - Choiriya Dwi Yusrowatin; Wahyu Setia Kuscahyaning Putri; Hilmy Aliriad (Universitas Hamzanwadi, 2026)
The effectiveness of gradually administering isotonic drinks for post-exercise cardiovascular recovery has not been empirically proven compared to consuming mineral water. This study aims to analyze the effectiveness of administering isotonic drinks at 5 different times compared to mineral water on heart rate recovery and aerobic capacity Vo₂max after 30 minutes of running. The research method used a quantitative true experiment design with a pretest-posttest control group involving 150 students divided into an experimental group 75 and a control group 75. Fluid intervention was administered according to a gradual protocol during the 30-minute running session. Resting heart rate and VO₂max were estimated using a 12-minute Cooper running test measured before and after the intervention. Data were analyzed using paired and independent sample T-tests. The results showed that the isotonic group experienced a significantly greater decrease in resting heart rate (-6.9±3.5 bpm) than the mineral water group (-4.3±3.1 bpm) with p=0.006. Heart rate recovery analysis confirmed a faster recovery pattern in the isotonic group. There was no significant difference in Vo₂max improvement between groups (p=0.081). The conclusion of this study proves that gradual administration of isotonic drinks is more effective than mineral water in accelerating cardiovascular recovery after a 30-minute run,